Application of non-woven aramid-polyimide composite materials for high reliability printed circuit boards for use in spacecraft electronics. (2021) - Muthulakshmi, B.; Hanumanth Rao, C.; Sharma, S.V.
Abstract: An understanding of the impact of current trends on composites begins with the PCB material and its manufacture. Discovery, development and application of new materials are the robust power for the development of human society. With recent advances in electronics materials and designs, the electronics industry is pushing the operating temperatures to new boundaries. Electronic packaging technology is under increasing pressure to downsize devices. New dielectric composite materials have been introduced for printed circuit board applications, such as Thermount polyimide with the aim to match the requirements for high speed and high density of electronic devices that are planned for new spacecraft electronic boards. The objective of the paper is to discuss about introduction and fabrication of non-woven aramid-polyimide composite material and experiment carried out to study the effect and its application in high reliability HDI PCBs for spacecraft electronics. An experiment is made to attempt realization of PCB using "Non-woven aramid-polyimide composite substrate" as an alternative to FR4 glass reinforced substrate to achieve improved thermal characteristics and also weight reduction, which is desirable for space electronics. From the experimental results, it is evident that, introduction of thermount polyimide material has significant weight reduction and the material withstood readily six dip thermal stress tests. It is found that the usage of the above substrate has enhanced the reliability and PCBs produced have proved the ability to withstand thermal variation commonly experienced by the high-speed electronics.